1998
DOI: 10.1021/ja980560m
|View full text |Cite
|
Sign up to set email alerts
|

Proportions of Species Observed in Jet Spectroscopy−Vibrational Energy Effects:  Histamine Tautomers and Conformers

Abstract: It has been found possible to understand the observed relative abundances of the several different tautomers and conformers observed in the millimeter-wave jet spectroscopy of histamine by using ab initio energy calculations at the MP2/6-311++G(d,p) level and including an estimate of thermal free energies. Conformational relaxation, previously found to be important for several molecules of comparable complexity, has been found to have a significant role in determining the relative abundances of histamine speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
154
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(160 citation statements)
references
References 13 publications
6
154
0
Order By: Relevance
“…The "effective population" of the observed conformers in the supersonic jet is a consequence of population due to their relative energies plus the possible contributions from relaxation of other conformers. 48,49 Using our nomenclature, the relative abundances estimated in experiments follow the ranking 1CaC1 > 1CbC1 ≈ 2TaC1 > 1CaT2 ≈ 2TbC1 > 1CbC3, with conformers attributed according to the MP2 calculations of the rotational constants. 15 Correlating relative free energies and abundances, this trend is in overall good agreement with the results obtained with metadynamics and the CHARMM26 force-field, with the exception of 1CbC3, which belongs to basin C and is thus lower in free energy than expected.…”
Section: Resultsmentioning
confidence: 94%
“…The "effective population" of the observed conformers in the supersonic jet is a consequence of population due to their relative energies plus the possible contributions from relaxation of other conformers. 48,49 Using our nomenclature, the relative abundances estimated in experiments follow the ranking 1CaC1 > 1CbC1 ≈ 2TaC1 > 1CaT2 ≈ 2TbC1 > 1CbC3, with conformers attributed according to the MP2 calculations of the rotational constants. 15 Correlating relative free energies and abundances, this trend is in overall good agreement with the results obtained with metadynamics and the CHARMM26 force-field, with the exception of 1CbC3, which belongs to basin C and is thus lower in free energy than expected.…”
Section: Resultsmentioning
confidence: 94%
“…17,[32][33][34][35] It arises from the need to both ͑a͒ heat the sample of molecules to obtain a gas-phase concentration that is sufficient for spectroscopic measurement and ͑b͒ cool the molecules to obtain a clear spectrum. This is illustrated for a typical IR or microwave spectroscopy experiment in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…17,[32][33][34][35] Conformers with large barriers to interconversion are expected to be trapped during cooling and maintain their original, high-temperature population. On the other hand, conformers exhibiting low-energy pathways leading to more stable structures are more likely to be missing from the final spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In particular, structures can be observed that have high potential energies and the observed structural distributions are therefore frequently not in thermal equilibrium with the other degrees of freedom. [2][3][4][5][6][7][8][9][10] This can be rationalized by the height of the barriers that separate potential energy minima which might be hard to overcome under the conditions prevailing in the molecular beam experiments. The study of the potential energy landscape of gas-phase molecules and the development of experimental methods to manipulate the conformational distribution of these species currently is an active field of research.…”
mentioning
confidence: 99%